Trials with the Haemonchus vaccine, Barbervax®, in ewes and lambs in a tropical environment: Nutrient supplementation improves protection in periparturient ewes - Bassetto, C. C. [UNESP]; Almeida, F. A. [UNESP]; Newlands, G. F.J.; Smith, W. D.; Castilhos, A. M. [UNESP]; Fernandes, S. [UNESP]; Siqueira, E. R. [UNESP]; Amarante, A. F.T. [UNESP] (Elsevier, 2018)
Haemonchus contortus is an economic problem in sheep farms worldwide, mainly in the tropics and subtropics. A vaccine against haemonchosis, called Barbervax®, was evaluated in ewes under two nutritional status, naturally infected with gastrointestinal nematodes. Ewes were divided into four groups: Supplemented Diet – Vaccine; Supplemented Diet – No vaccine; Basal Diet – Vaccine and Basal Diet – No vaccine. Their lambs were divided in Vaccinated and No vaccine. Ewes were immunised six times starting about 1 month of pregnancy with the first three doses at 3 week intervals and the last three shots at 4 week intervals. Supplemented ewes had higher body weight, body score and packed cell volume compared with those fed a basal diet. Both groups of vaccinated ewes showed a similar response in circulating anti-vaccine antibodies but the vaccine had no discernible effect on either body weight, body score and packed cell volume. There was a marked group difference in the number of ewes that received precautionary treatments with anthelmintic. All 14 Basal Diet – No vaccine ewes required treatment. In contrast only 7 ewes, in the Supplemented Diet – Vaccine group required anthelmintic treatment. In the Basal Diet – Vaccine and in the Supplemented Diet – No Vaccine groups, 12 and 13 ewes needed anthelmintic treatment, respectively. Vaccinated lambs showed much higher antibody titres resulting in 80% less Haemonchus spp. egg counts comparing with no vaccine lambs. Taken together these results clearly suggest that in pregnant and lactating ewes a combined protective effect between vaccination and improved nutrition resulted in fewer precautionary anthelmintic treatments. Thus, it was possible to achieve a more sustainable level of control of the haemonchosis, less dependent on anthelmintic drugs.
Keywords: Haemonchosis; Improved nutrition; Parasitic gastroenteritis; Prophylaxis; Sheep